Roles of Testosterone and Estradiol in Mediation of Acute Neuroendocrine and Electroencephalographic Effects of Sevoflurane During the Sensitive Period in Rats - Li, Ningtao; Xu, Ning; Lin, Yunan; Lei, Lei; Ju, Ling-Sha; Morey, Timothy E.; Gravenstein, Nikolaus; Zhang, Jiaqiang; Martynyuk, Anatoly E. (Frontiers in Endocrinology, 2020)
Testosterone (T), acting through its derivative 17β-estradiol (E2), regulates the brain’s sexual differentiation in rodents during the perinatal sensitive period, which mirrors the window of vulnerability to the adverse effects of general anesthetics. The mechanisms of anesthesia’s adverse effects are poorly understood. We investigated whether sevoflurane alters T and E2 levels and whether they contribute to sevoflurane’s acute adverse effects in postnatal day 5 Sprague-Dawley rats. The rats underwent electroencephalography recordings for 2 h of baseline activity or for 1 h before and another hour during 2.1% sevoflurane exposure, followed by collection of trunk blood and brain tissue. Pharmacological agents, including the GABA type A receptor inhibitor bicuculline and the aromatase inhibitor formestane, were administered 30 min before sevoflurane anesthesia. Sevoflurane increased serum T levels in males only. All other effects of sevoflurane were similar in both sexes, including increases in serum levels of E2, hypothalamic mRNA levels of aromatase, estrogen receptor α (Erα) [not estrogen receptor  (Er)], Na+-K+-Cl- cotransporter (Nkcc1)/K+-Cl- cotransporter (Kcc2) mRNA ratio, electroencephalography-detectable seizures, and stress-like corticosterone secretion. Bicuculline and formestane alleviated these effects, except the T level increases. The ERα antagonist MPP, but not the ER antagonist PHTPP, reduced electroencephalography-detectable seizures and normalized the Nkcc1/Kcc2 mRNA ratio. Collectively, sevoflurane exacerbates levels of T in males and E2 in both sexes during the period of their organizational effects in rodents. Sevoflurane acts through GABAAR-mediated, systemic T-independent elevation of E2 to cause electroencephalography-detectable seizures, stress-like corticosterone secretion, and changes in the expression of genes critical for brain development.